Mapping Digital and Omnichannel Strategy Models through Customer Engagement and Technology: An Empirical Study on the East Java Retail Industry - Donny Arif (Universitas Nahdlatul Ulama Surabaya, 2026)
This study examines the influence of digital transformation and omnichannel strategies on retail sales performance in East Java, considering customer engagement as a mediating variable and technological competence as a moderating variable. The background of this study was driven by the disruption following the COVID-19 pandemic, which led many large retailers to close because they failed to adapt. At the same time, e-commerce transactions increased rapidly, and consumer shopping patterns shifted. This study aims to develop an integrative model that explains how digitalization and omnichannel strategies increase sales through customer engagement and organizational technological capabilities. The method used is a quantitative explanatory approach employing SEM-PLS, involving approximately 100 respondents from East Java retail MSMEs that have adopted both digital and physical channels. The novelty of this study lies in its use of a moderated mediation model, which is rarely used in the context of Indonesian retail MSMEs, and in its focus on the local context of East Java. We expect to deliver a digital-omnichannel strategy model grounded in engagement and technological competence, publish reputable international articles (Scopus-indexed), produce a policy brief for policymakers, and create a practical guide for MSMEs. This research is also part of a five-year research roadmap that aims to develop a sustainable digital retail ecosystem based on AI and consumer behavior prediction..